Index to Vigiliae Christianae Volumes 1-50 (1947-1996) - Oort, J. van, (Biblical Studies, Ancient Near East and Early Christianity - Book Archive pre-2000., 1996)
This index provides the reader with a detailed survey of fifty years of scholarly work as published in the leading journal in the field of Patristic and Early Christian studies. One of the most valuable features of this volume is the exhaustive index on patristic sources which have been treated in the journal during the past fifty years. The volume further contains indexes on classical sources, and on biblical texts and jewish sources, as well as full indexes of all the authors, articles, and book reviews. The publication of this index gives you the opportunity to add enormous value to the collection of Vigiliae Christianae volumes on your shelves.